2009
DOI: 10.1016/j.devcel.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cellular Protrusions Branch Out

Abstract: F-BAR domains bind curved membranes and induce membrane invagination. In a recent Cell paper, Guerrier et al. describe an “inverse” F-BAR family member that induces outward curvature and filopodia in migrating neurons. These findings suggest that F-BAR domains are functionally diverse and regulate different types of membrane morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Analyses of the F-BAR domain in proteins such as FBP17 and srGAP2 have shown that it can either produce invagination or evagination of membranes (Kamioka et al, 2004; Tsujita et al, 2006; Carlson and Soderling, 2009; Guerrier et al, 2009). This possibility for WRP was tested in cell-based assays for WRP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the F-BAR domain in proteins such as FBP17 and srGAP2 have shown that it can either produce invagination or evagination of membranes (Kamioka et al, 2004; Tsujita et al, 2006; Carlson and Soderling, 2009; Guerrier et al, 2009). This possibility for WRP was tested in cell-based assays for WRP.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, a recent study of srGAP2 showed that its F-BAR domain enhances outward membrane protrusions (Guerrier et al, 2009). Because the membrane topology facilitated by the F-BAR domain of srGAP2 is opposite of other F-BAR domains, it has been termed an inverse F-BAR or inverse F-BAR (IF-BAR) domain (Carlson and Soderling, 2009). Yet, how common the IF-BAR domain is or what the physiological functions of these domains are remains very unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This force may be mediated by the BAR-domain superfamily of proteins, a group of molecules that control curvature of the plasma membrane ( Fig. 2B; Guerrier et al, 2009;Carlson & Soderling, 2009). The balance of expansion and contraction may give rise to rapid fluctuation, or morphing, of spines within 1 min (Matus, 2000).…”
Section: Molecular Bases Of Spine Persistence and 'Intrinsic Fluctuatmentioning
confidence: 99%
“…Surprisingly, a recent study of the related srGAP2 showed that its F-BAR domain enhances outward membrane protrusions that appear similar to that of filopodia (Guerrier et al, 2009). Because the membrane topology facilitated by the F-BAR domain of srGAP2 is opposite of other F-BAR domains it has been termed an Inverse F-BAR or IF-BAR domain (Carlson and Soderling, 2009). Yet what the physiological function of this domain is remains very unclear.…”
Section: Regulation Of Spine Formation and Function By The Candidate mentioning
confidence: 99%